A mutation specific polymerase chain reaction for detecting hepatitis B virus genome mutations at nt551 - Ma, Chun-Ling (World J Gastroenterol, 2003)
AIM: The hepatitis B surface antigen (HBsAg) is considered to be one of the best markers for the diagnosis of acute and chronic HBV infection. But in some patients, this antigen cannot be detected by routine serological assays despite the presence of virus. One of the most important explanations for the lack of detectable HBsAg is that mutations which occur within the “a” determinant of HBV S gene can alter expression of HBsAg and lead to changes of antigenicity and immunogenicity of HBsAg accordingly. As a result, these mutants cannot be detected by diagnosis assays. Thus, it is essential to find out specific and sensitive methods to test the new mutants and further investigate their distribution. This study is to establish a method to investigate the distribution of the HBsAg mutant at nt551. METHODS: A mutation specific polymerase chain reaction (msPCR) was established for amplifying HBV DNA with a mutation at nt551. Four sets of primer pairs, P551A-PPS, P551G-PPS, P551C-PPS and P551T-PPS, with the same sequences except for one base at 3’ terminus were designed and synthesized according to the known HBV genome sequences and the popular HBV subtypes, adr and adw, in China. At the basis of regular PCR method, we explored the specific conditions for amplifying HBV DNAs with a mutation at nt551 by regulating annealing temperature and the concentration of these primers. 126 serum samples from patients of hepatitis B were collected, among which 16 were positive for HBV S DNA in the nested PCR amplification. These 16 HBV S DNAs were detected by using the msPCR method. RESULTS: When the annealing temperature was raised to 71 °C, nt551A and nt551G were amplified specifically by P551A-PPS and P551G-PPS; At 72 °C and 5 pmole of the primers (each) in reaction of 25 μl volume, nt551C and nt551T were amplified specifically by P551C-PPS and P551T-PPS. 16 of HBV S gene fragments were characterized by using this method. 14 of them were positive for nt551A, one was positive for nt551G, and the other one was positive for nt551T. The results were confirmed by nucleotide sequencing. CONCLUSION: The mutation specific polymerase chain reaction is a specific and sensitive method for detecting the mutations of HBV genome at nt551.